Mild Microwave-Assisted Synthesis of Dipyrromethanes and Their Analogues - Xiong, Ruisheng; Borbas, K. Eszter (Synlett, 2015)
The Mannich reaction between pyrroles or indoles and Eschenmoser’s salt (dimethylmethylideneammonium iodide) forms N,N-dimethylamino-methylated derivatives in good to excellent yields. The reaction is highly regioselective, and for pyrroles both 2- and 3-substituted derivatives could be obtained. The N,N-dimethylaminomethylpyrroles and indoles underwent substitution with pyrrole under microwave irradiation, affording the appropriate dipyrromethanes, N-confused, and indolo-dipyrromethanes in moderate to excellent overall yield.
Keywords: pyrroles; indoles; heterocycles; microwave synthesis; dipyrromethanes